Elderly rats fed with a high-fat high-sucrose diet developed sex-dependent metabolic syndrome regardless of long-term metformin and liraglutide treatment - Ivić, Vedrana; Zjalić, Milorad; Blažetić, Senka; Fenrich, Matija; Labak, Irena; Scitovski, Rudolf; Szűcs, Kálmán Ferenc; Ducza, Eszter; Tábi, Tamás; Bagamery, Fruzsina; Szökő, Éva; Vuković, Rosemary; et al. (Frontiers in Endocrinology, 2023)
The aim of the study was to determine the effectiveness of early antidiabetic therapy in reversing metabolic changes caused by high-fat and high-sucrose diet (HFHSD) in both sexes. Elderly Sprague-Dawley rats, 45 weeks old, were randomized into 4 groups: a control group fed on the standard diet (STD), one group fed the HFHSD, and two groups fed the HFHSD along with long-term treatment of either metformin (HFHSD+M), or liraglutide (HFHSD+L). Antidiabetic treatment started 5 weeks after introduction of diet and lasted 13 weeks, until the animals were 64 weeks old. Unexpectedly, HFHSD fed animals did not gain weight, but nevertheless underwent significant metabolic change. Both antidiabetic treatments produced sex-specific effects, but neither prevented onset of prediabetes nor diabetes. Liraglutide vested benefits to liver and skeletal muscle tissue in males, but induced signs of insulin resistance in females.